Antioxidative peptides from fish sauce by-product: Isolation and characterization - Choksawangkarn, Waeowalee; Phiphattananukoon, Susanee; Jaresitthikunchai, Janthima; Roytrakul, Sittiruk (Agriculture and Natural Resources, 2018)
Fish sauce by-product (FSB) refers to solid waste from fish sauce industry. It is composed of nutritionally important biomolecules; however, FSB is currently undervalued. FSB contains natural protein hydrolysate produced from digestion of fish proteins using various proteases from their digestive system and halophiles in the fermentation tank. This study focused on the potential use of FSB from the lowest grade fish sauce production as a source of bioactive peptides. The results showed that the FSB extract contained about 10% (weight per volume) protein and the sodium dodecyl sulfate-polyacrylamide gel electrophoresis profile was similar to that of fish sauce. The antioxidant activity of the FSB extract was determined using 2,2-diphenyl-1-picrylhydrazyl radical scavenging assay. The two most effective fractions had half maximal inhibition values of 0.57 ± 0.05 mg/mL and 1.25 ± 0.16 mg/mL. Upon digestion with Proteinase K, the activity decreased, suggesting that active molecules were derived from proteins or peptides. The low molecular weight FSB fraction contained potent antioxidative molecules, which were identified as PQLLLLLL and LLLLLLL. The study provided useful information for future development of value-added products from the solid waste produced during fish sauce manufacturing, which is one of the important marine industries in Southeast Asia.